RNA-binding proteins in bone pathophysiology - Maroni, Paola; Pesce, Noemi Anna; Lombardi, Giovanni (Frontiers in Cell and Developmental Biology, 2024)
Bone remodelling is a highly regulated process that maintains mineral homeostasis and preserves bone integrity. During this process, intricate communication among all bone cells is required. Indeed, adapt to changing functional situations in the bone, the resorption activity of osteoclasts is tightly balanced with the bone formation activity of osteoblasts. Recent studies have reported that RNA Binding Proteins (RBPs) are involved in bone cell activity regulation. RBPs are critical effectors of gene expression and essential regulators of cell fate decision, due to their ability to bind and regulate the activity of cellular RNAs. Thus, a better understanding of these regulation mechanisms at molecular and cellular levels could generate new knowledge on the pathophysiologic conditions of bone. In this Review, we provide an overview of the basic properties and functions of selected RBPs, focusing on their physiological and pathological roles in the bone.